2020
DOI: 10.3390/ijms21020452
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CFTR Biogenesis by the Proteostatic Network and Pharmacological Modulators

Abstract: Cystic fibrosis (CF) is the most common lethal inherited disease among Caucasians in North America and a significant portion of Europe. The disease arises from one of many mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator, or CFTR. The most common disease-associated allele, F508del, along with several other mutations affect the folding, transport, and stability of CFTR as it transits from the endoplasmic reticulum (ER) to the plasma membrane, where it functions primarily as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 209 publications
(210 reference statements)
0
37
0
Order By: Relevance
“…In the literature, the transcriptional and post-transcriptional CFTR regulation pathway is well described [ 88 ]. Misfolded F508del-CFTR is sequestered in the ER and then degraded through the ER-associated degradation (ERAD) pathway, which involves many co-chaperones [ 89 ]. Although our RNA-seq data revealed that a number of proteins that interact with CFTR were differentially regulated in UNC- and SC-grown epithelia ( Table S6 ), it is unclear whether enhanced protein degradation via ERAD could account for our results.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the transcriptional and post-transcriptional CFTR regulation pathway is well described [ 88 ]. Misfolded F508del-CFTR is sequestered in the ER and then degraded through the ER-associated degradation (ERAD) pathway, which involves many co-chaperones [ 89 ]. Although our RNA-seq data revealed that a number of proteins that interact with CFTR were differentially regulated in UNC- and SC-grown epithelia ( Table S6 ), it is unclear whether enhanced protein degradation via ERAD could account for our results.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the family of ATP-binding cassette (ABC) transporters (CFTR is alternately known as ABC subfamily C member 7 (ABCC7)) and functions as a cyclic adenosine monophosphate (cAMP)-dependent chloride channel that may open on the cell surface of epithelial cells. This chloride channel is necessary to maintain an alkaline pH and dilute fluid secretions [ 4 ] via a passive Cl − /HCO3 − anion exchange on exocrine epithelia along their electrochemical gradient [ 5 , 6 ]. Defects of CFTR may lead to dehydration of secretions and hyperviscous mucus, causing a multisystem disease with major affections of the respiratory, gastrointestinal, and hepatobiliary tract.…”
Section: Introductionmentioning
confidence: 99%
“…Early on, the folding defect associated with F508del was shown to be partially rescued by incubating the cells at 27°C (6), which is believed to stabilize key limiting folding intermediates and lead to the partial maturation of the protein. Rescue could also be achieved with small molecules such as chemical chaperones, one of the best examples being glycerol (7). These observations led to the screening of small molecules favoring the proper folding of mutant CFTR and to the identification of drugs named correctors, such as VX-809 (Lumacaftor) or its structurally closely related analogue VX-661 (Tezacaftor).…”
Section: Introductionmentioning
confidence: 99%